Integrated Public Service Analysis of South Bengkulu Police Station - Purba, David Pratama (Sahabat Publikasi, 2024)
In the digital age, technological advancements have led to the widespread use of information systems and technology (IS/IT) to enhance public services. Implementing e-government has become crucial in supporting good governance, particularly in Government-to-Employee (G2E) and Government-to-Citizen (G2C). This study focuses on the South Bengkulu Police Station's Information System/Information Tech utilization to improve public service delivery. Through an analysis of the station's public service processes using SWOT and PEST analysis, this research aims to identify existing efforts in service development. It also aims to propose a concept for integrated public services. The findings of this analysis offer insights into optimizing police performance, benefiting the general public and internal stakeholders. However, certain limitations are acknowledged, including the lack of in-depth analysis of public service system performance and the creation of integrated service design concepts.